The effect of body composition on pulmonary function in elite athletes - Kocahan, Tuğba; Akınoğlu, Bihter (Progress in Nutrition, 2019)
The pulmonary function is one of the most basic factors that determine athletic performance. The purpose of this study was to investigate the correlation of the body weight, body fat percentage (fat%), body fat mass, fat-free mass, muscle mass, abdominal muscle mass, and waist and hip circumference on the forced expiratory volume curve and maximal voluntary ventilation. A total of 398 elite athletes composed of 254 male and 144 female (mean age, 16.63±2.28 years) were enrolled for this study. The study involved the measurements of the body composition by bioelectrical impedance method, and forced vital capacity (FVC); forced expiratory volume at 1 second (FEV1); forced expiratory flow during the middle half of the FVC (FEF25-75) from the forced expiratory volume curve; and maximal voluntary ventilation (MVV) by spirometry. Correlation and multiple regression analysis between the body composition and pulmonary function were used. It was determined that there was an important relationship between the demographic characteristics and body composition parameters of the athletes and the pulmonary function test values. This relationship was categorized as low, medium, high and very high (p